Controle de Dalbulus maidis (DeLong & Wolcott) (Hemíptera: Cicadellidae) na cultura do milho com pulverização eletrostática - Marques, Rodrigo Santos (2018)
Among the pests that attack the maize crop, the maize leafhopper, which causes direct damages by sap sucking and indirect ones, stands out as being a vector of pathogens and viruses, and can cause losses of up to 100% of the production. An alternative to improve the chemical control of this pest is the use of electrostatic spraying technology, however, there is no research support. This study aimed to evaluate the deposition of spray in the maize crop and the effectiveness in the chemical control of the maize leafhopper, using the electrostatic spraying system, at different application rates, compared to the conventional spraying system. The experiment was conducted in a randomized block design with five treatments, in a 2x2 + 2 factorial scheme: presence or absence of electrostatic spraying system, two application rates (35 and 50 L ha-1), an additional treatment using a hydraulic spraying and a rate of 100 L ha-1, and other additional treatment without the application of insecticide, in order to support the study of pest infestation. Each treatment consisted of eight replicates, in which the spray deposition in the maize canopy and the efficiency in the control were evaluated. For the insecticide applications, a rod sprayer with induction electrostatic spraying system was used with indirect electrification. To evaluate the deposition, the Brilliant Blue FCF marker was added to the spray to be detected by absorbance in spectrophotometry. For the efficacy control of the maize leafhopper, the insecticide composed of thiamethoxam and lambda-cyhalothrin was used, comparing with the control without the application. There was a significant increase in the spray deposition, both in the upper and lower maize leaves, with the use of electrostatic spray technology compared to the conventional spray system. The crop protection control of the maize leafhopper was also superior. The electrostatic spraying also made it possible to reduce the application rate by approximately three times in relation to that used in conventional hydraulic spraying.